Davita's harp - Potok, Chaim (New York : Knopf, 1985)
The daughter if a non-believing Jewish mother and a non-believing gentle father - dedicated Communists both - Davita Chandel, growing up as the world suffers through the Spanish Civil War and World War II, turns to Judaism for consolation and spiritual sustenance.
Keywords: Communists -- United States -- Fiction; Parent and child -- United States -- Fiction; Judaism -- Customs and practices -- Fiction; Faith -- Fiction